A Case Report on the Surgical Treatment of Scoliosis and Kyphosis Caused by Congenital Multiple Butterfly Vertebrae - Cai, Xuan; Zhang, Nian; Lu, Yi Jun; Zhang, Bo Weng; Chen, Zaifei (Journal of Contemporary Medical Practice, 2025)
Case: A 14-year-old adolescent patient presented with recurrent chest and lower back pain. Over a year ago, a kyphosis and a scoliotic deformity resembling a knife-back were detected at the thoracolumbar junction. Further examination revealed a diagnosis of hemivertebrae formation in the thoracic vertebrae, scoliosis, and kyphosis in the thoracolumbar region, caused by a rare developmental anomaly of multiple butterfly vertebrae. After confirmation of the diagnosis, the patient underwent surgical treatment, and the condition was effectively alleviated.